2018
DOI: 10.1111/epp.12450
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Ralstonia solanacearum and Ralstonia pseudosolanacearum in drain water

Abstract: The survival in drain water of two strains of Ralstonia solanacearum and three strains of Ralstonia pseudosolanacearum, including two strains able to cause wilt in roses, was determined. Water draining from drip‐irrigated rock wool mats on which roses were grown was supplemented with the pathogen and survival was monitored at 4, 12, 20 and 28°C for up to 112 days. All strains were able to survive for at least 112 days in drain water at 12 and 20°C, but at 4°C maximum survival was 56 days. At 28°C, the survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…Whereas for the SRP, we observed a faster decline within 4 days at a higher temperature (25˚C) and a better persistence at the lower temperature in natural TDW. Nevertheless, the temperature effect on the die-off of the SRP was negligible in autoclaved TDW microcosms, when comparing the inactivation curves at 10 and 25˚C (see S1 Fig) . The long-term persistence in sterile aquatic microcosms, where the indigenous microbiota was absent, has been shown earlier for the SRP [25,51], as well as for R. solanacearum [22][23][24]. In addition, our results demonstrated that D. solani can persist in sterile autoclaved water for a prolonged time which seem to contrast with the findings of van Doorn et al [25] where Dickeya spp.…”
Section: Influence Of Microbiotacontrasting
confidence: 71%
See 1 more Smart Citation
“…Whereas for the SRP, we observed a faster decline within 4 days at a higher temperature (25˚C) and a better persistence at the lower temperature in natural TDW. Nevertheless, the temperature effect on the die-off of the SRP was negligible in autoclaved TDW microcosms, when comparing the inactivation curves at 10 and 25˚C (see S1 Fig) . The long-term persistence in sterile aquatic microcosms, where the indigenous microbiota was absent, has been shown earlier for the SRP [25,51], as well as for R. solanacearum [22][23][24]. In addition, our results demonstrated that D. solani can persist in sterile autoclaved water for a prolonged time which seem to contrast with the findings of van Doorn et al [25] where Dickeya spp.…”
Section: Influence Of Microbiotacontrasting
confidence: 71%
“…Few studies investigated the die-off of R. solanacearum in natural water types such as river water [22], agricultural drainage water [23], or drainage water leaching from rock wool in a rose-growing greenhouse [24]. The results of these studies showed that temperature and the natural microbiota have a significant effect on the die-off of R. solanacearum in non-sterile microcosms compared with sterile conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of nonresuscitatable VBNCs were calculated by comparing the16S rRNA copy number against the control by the formula: [(RNA copies of N th day/sample treatments X 100)/ RNA copies of N th day/control].ResultsCon rmation of VBNCs after psychrophilic stressThe formation of VBNC is genus, strain and stress dependent. Microcosms of RSSC incubated at psychrophilic temperatures lose their culturability within 150 days(van Overbeek et al 2004;Stevens et al 2018). In this investigation, the total loss of culturability was noticed on 180 th day in both the strains.…”
mentioning
confidence: 54%
“…If a symptomatic tomato plant is positioned between healthy tomato plants in an aquaponic culture, neighbouring pathogen‐free plants became symptomatic after 8 days (Jenkins & Averre, 1983). Additionally, RSSC strains can persist in water for varying periods of time from a week to months and this persistence is affected by various environmental conditions such as temperature, light, salinity and the composition of the microflora, including lytic bacteriophages, protozoa and other bacteria (Van Overbeek et al ., 2004; Álvarez et al ., 2007; Stevens et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%